Post-occupancy evaluation in architecture: experiences and perspectives from UK practice. Issue 6 (18th August 2018) - Hay, Rowena; Samuel, Flora; Watson, Kelly J.; Bradbury, Simon
ABSTRACT: The importance of post-occupancy evaluation (POE) is widely acknowledged in the academic literature, industry press and, increasingly, by professional institutes. Learning from previous projects systematically is central to improving building performance, resulting in a built environment that better fits the needs of clients, end users, wider society and the environment. The key role of architects in pushing forward this agenda has been recognized, however evidence suggests that take up of POE is low across the profession. Whilst research has investigated barriers to POE across the construction industry, very little has considered the unique perspective of architects. In-depth interviews with UK-based architects are presented to explore their experiences in relation to POE and their perspectives on its potential to be a standard part of architectural practice. The findings indicate that a considerable amount of practical work is being undertaken, but uncertainty over what constitutes POE means it is often excluded from the POE label – with significant implications for the development of a rigorous evidence base. An appetite is identified for more holistic evaluation measures that move beyond the current preoccupation with energy efficiency to consider other aspects of building performance, and thereby sustainability, in a wider value framework.